Kajian Prospek Usaha Tanaman Hias Akuarium pada Kelompok Usaha Bunga Air “Aqua Plantindo” di Ciawi Kabupaten Bogor - Bambang Sukaca; Muhammad Syamsun; Illah Sailah (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
Study of Aquarium Decorative Plant Business Prospect at Bunga Air “Aqua Plantindo” Business Group in Ciawi, Bogor Regency aims to identify the business feasibility in business development, formulating the right strategy in the business development, to evaluate the performance of Bunga Air “Aqua Plantindo” Business Group by using Balanced Scorecard (BSC) approach and to identify partnership level category of aquarium decorative plant small industry. The result study was obtained the Net Present Value (NPV) of Rp. 188.455.000,00, Internal Rate of Return (IRR) 38,63%, Profitability Index (PI) 1,15 and Net B/C ratio 1,67, indicating the this business is considered to be feasible to be grown. Calculation result of payback (PBP) this period was identified that the investment payback period is 2 years 3 months 18 days and shorter than investment life period for 5 years, so it is feasible and profitable. Based on result of strategy analysis by using Strenghts, Weaknesess, Opportunities and Threats (SWOT) analysis, the right strategy in the business development of Bunga Air “Aqua Plantindo” Business Group by maintaining and improving product quality in accordance with the customers wants, maintaining and improving the business/partnership relations with exporters and suppliers. The result of the analysis of Internal-External (IE) matrix showed an internal factor of 2.702 and an external factor of 2.516, which put the business in quadrant V, which are growth and stability. It means they must defend strategy that they have been using up till now, and they must increase developing strategy of business. Result of evaluation with  Balanced Scorecard (BSC) indicates that financial performance from 2003-2007 in aquarium decorative plant business at  Bunga Air “Aqua Plantindo” Business Group was fairly good seen from liquidity, solvability, efficiency in taking advantage of assets,  net profits obtained, effectiveness and productivity in making use of assets owned and in receivables collection. Based on the result of study from customer perception with six attribute dimensions the service quality is fairly satisfactory. Seeing from after sales service level, operation/production process and innovation process show that internal business of Bunga Air “Aqua Plantindo” Business Group is considered fairly good. Observing from performance aspect, organizational restructuring aspect, learning dynamic aspect, group member satisfaction level aspect, knowledge management aspect, empowerment aspect and technology application aspect indicate that from growth and learning perspectives at Bunga Air “Aqua Plantindo” Business Group is considered fairly good. Partnership level between Bunga Air “Aqua Plantindo” Business Group with PT. Nusantara Aquatic Exporindo and CV. Cahaya Baru is included in First Prime Partnership Level. While the partnership level between Bunga Air “Aqua Plantindo” Business Group with CV. Tropical Aquatic is included in Secondary Prime Partnership Level.